2021
DOI: 10.1111/jre.12871
|View full text |Cite
|
Sign up to set email alerts
|

Different applications forms of green tea (Camelliasinensis (L.) Kuntze) for the treatment of periodontitis: a systematic review and meta‐analysis

Abstract: Background Scaling and root planning (SRP) is the gold standard for non‐surgical periodontal treatment. Green tea as a supporting alternative in non‐surgical periodontal treatment has been suggested as a therapeutic option in the treatment of periodontitis. Objective To analyse the comparative effectiveness of green tea (Camellia sinensis) in its different forms and applications for the treatment of periodontitis. Methods We included randomized clinical trials evaluating green tea as an adjuvant therapeutic ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…3 Anatomy of the roots, furcation, and morphology of the periodontal pocket make a negative impact on the elimination of the pathogen biofilm and thus treatment outcomes. 3,4 Although, conventional non-surgical therapies are an effective approach to eliminating the infection, 5,6 it creates a wound in the already inflamed periodontal tissue, and the restoration of this tissue depends largely on favorable cellular and molecular responses. 7,8 Due to these limitations of non-surgical periodontal treatment, new techniques have been investigated to improve the treatment outcome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Anatomy of the roots, furcation, and morphology of the periodontal pocket make a negative impact on the elimination of the pathogen biofilm and thus treatment outcomes. 3,4 Although, conventional non-surgical therapies are an effective approach to eliminating the infection, 5,6 it creates a wound in the already inflamed periodontal tissue, and the restoration of this tissue depends largely on favorable cellular and molecular responses. 7,8 Due to these limitations of non-surgical periodontal treatment, new techniques have been investigated to improve the treatment outcome.…”
Section: Introductionmentioning
confidence: 99%
“…SRP is reported as the basic treatment method and a gold standard for non‐surgical periodontal treatment by removing or reducing subgingival bacterial biofilm and other factors that are known to cause gingival inflammation 3 . Anatomy of the roots, furcation, and morphology of the periodontal pocket make a negative impact on the elimination of the pathogen biofilm and thus treatment outcomes 3,4 . Although, conventional non‐surgical therapies are an effective approach to eliminating the infection, 5,6 it creates a wound in the already inflamed periodontal tissue, and the restoration of this tissue depends largely on favorable cellular and molecular responses 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…In this meta-analysis study (included 9 studies), 5 clinical parameters were used to evaluate the effect of green tea. Due to short follow-up periods, the accuracy of these included articles is low and very low according to the GRADE tool and clinical parameters and is not reliable to evaluate the response to treatment and start the healing process; accordingly, it seems that using a molecular assay tool is logical [ 16 ]. In a similar meta-analysis, Mazur et al examined the antiperiodontitis and anticaries effects of green tea.…”
Section: Discussionmentioning
confidence: 99%
“…The main constituent of green tea that expresses many of the anti-carcinogenesis actions is EGCG. EGCG can regulate the expression of the epidermal growth factor receptor (EGFR) [75,76], the NF-κB and AP-1 factors reducing the tumoral cell's proliferation and migration [63]. In Irimie's study, ECGC has been shown to cause tumor cell death inducing apoptosis and autophagy [77].…”
Section: Green Teamentioning
confidence: 99%